Pseudotumor cerebri syndrome in childhood: incidence, clinical profile and risk factors in a national prospective population-based cohort study - Matthews, Yim-Yee; Dean, Fiona; Lim, Ming J.; Mclachlan, Karen; Rigby, Alan S.; Solanki, Guirish A.; White, Catherine P.; Whitehouse, William P.; Kennedy, Colin R. (BMJ, 2017)
AIM: To investigate the epidemiology, clinical profile and risk factors of pseudotumor cerebri syndrome (PTCS) in children aged 1-16 years.